Systematic review of purine analog treatment for chronic lymphocytic leukemia: lessons for future trials. - CLL Trialists’ Collaborative Group (2012)
A systematic review of purine analogs revealed heterogeneity between trials in treatment effects on response and progression free survival, but not survival, perhaps partly due to variations in analytical methods. In addition, combination treatments required evaluation. Therefore, individual patient data were sought for all randomized trials in untreated chronic lymphocytic leukemia which involved a purine analog, but which did not include antibody therapies. Sixteen trials were found, addressing seven comparisons. Eight trials, with 2,753 patients, showed that single agent purine analog improved progression free survival (odds ratio=0.71; 95% confidence interval=0.63-0.79). Heterogeneity remained substantial. Three trials, with 1,403 patients, showed that progression free survival was further improved by the addition of cyclophosphamide (odds ratio=0.54; 0.47-0.62). Fewer data were available on the addition of other drugs to purine analog, and none showed clear benefit. Two trials, with 544 patients, suggested cladribine improved progression free survival compared to fludarabine (odds ratio=0.77; 0.63-0.95). No differences were seen in overall survival for any comparisons. In conclusion, purine analogs, particularly combined with cyclophosphamide, significantly improve progression free survival but not survival. Some groups, such as the elderly, may not see the same benefits and maximizing doses may be important for all treatments, including chlorambucil. Longer follow up, consistent definitions and detailed reporting of trials should be encouraged.